Elevated IgA Plasmablast Levels in Subjects at Risk of Developing Rheumatoid Arthritis. Issue 10 (28th September 2016) - Kinslow, Jennifer D.; Blum, Lisa K.; Deane, Kevin D.; Demoruelle, M. Kristen; Okamoto, Yuko; Parish, Mark C.; Kongpachith, Sarah; Lahey, Lauren J.; Norris, Jill M.; Robinson, William H.; Holers, V. Michael
Abstract : Objective: The disease process in rheumatoid arthritis (RA) starts years before the clinical diagnosis is made, and elevated levels of disease‐specific autoantibodies can be detected during this period. Early responses to known or novel autoantigens likely drive the eventual production of pathogenic autoimmunity. Importantly, the presence of disease‐specific autoantibodies can identify individuals who are at high risk of developing RA but who do not currently have arthritis. The goal of the current study was to characterize plasmablasts from individuals at risk of developing RA. Methods: We investigated antibody‐secreting plasmablasts derived from a well‐characterized cohort of individuals who were at risk of developing RA, based on RA‐related serum autoantibody positivity, as compared to patients with early (<1 year) seropositive RA as well as healthy control subjects. The plasmablast antibody repertoires of at‐risk subjects were analyzed using DNA barcode–based methods with paired heavy‐ and light‐chain gene sequencing. Cells were single‐cell sorted, the cell‐ and plate‐specific DNA barcodes were sequentially added, and next‐generation sequencing was performed. Results: Total plasmablast levels were similar in the antibody‐positive (1%) and control (0.4–1.6%) groups. However, increased frequencies of IgA+ versus IgG+ plasmablasts were observed in the antibody‐positive group (39% IgA+ and 37% IgG+) as compared to other groups (1–9% IgA+ and 71‐87% IgG+). Paired antibody sequences from antibody‐positive subjects revealed cross‐isotype clonal families and similar sequence characteristics in the IgA and IgG plasmablast repertoires. Antibody‐positive individuals also demonstrated elevated serum levels of IgA isotype anti–cyclic citrullinated peptide 3 antibodies. Conclusion: The IgA plasmablast dominance in these antibody‐positive individuals suggests that a subset of RA‐related autoantibodies may arise from mucosal immune responses and may be involved in early disease pathogenesis in individuals who are at risk of developing RA.